Parallel boundary element method for solving laplace equation - Nur Farahin Abd Razak, 1993-; Yeak Su Hoe, supervisor; Fakulti Sains (2016)
Project Paper (Sarjana Muda Sains (Matematik Industri)) - Universiti Teknologi Malaysia, 2016